An integrated facility management system (IFMS), supported by the virtual design and construction framework (VDC), for engineering laboratories - Bazan Montalto, Alvaro Daniel (2024)
Construction has always been characterized as a fragmented, complex, and challenging industry. This has been reflected throughout the life cycle of construction projects, whether in design, construction, or operation and maintenance (O&M). Although efforts have been made to identify and solve problems in design and construction, there is a high degree of disconnection and lack of consensus in the O&M stage, represented by Facility Management (FM). This paper carries out a bibliographic review of the challenges and problems faced by facility management and the methods and technologies proposed for their solution. Moreover, an introduction to Virtual Design and Construction is made as an emerging methodology showing interesting results in the design and construction stages. The hypothesis is that the same positive results can be obtained if VDC were applied to an O&M stage. Finally, an Integrated Facility Management System (IFMS) is proposed based on the VDC methodology applied to O&M to integrate the building product, organization, and processes of an engineering laboratory facility in Lima, Peru.